Temporal variations in the atmospheric pressure curve in the Bydgoszcz area - Łaszyca, Edward (Bulletin of Geography. Physical Geography Series, 2022)
Atmospheric pressure, the meteorological parameter describing pressure conditions in an area, was analysed based on daily values. The mean atmospheric pressure in the Bydgoszcz area in the examined multi-annual period from 1971 to 2010 was 1006.4 hPa. Comparison of the mean value of atmospheric pressure calculated for the periods from 1971 to 1990 and from 1991 to 2010 revealed bi-directional differences between them. The atmospheric pressure curve featured high yearto-year variability in the examined 40-year period. In Bydgoszcz, there was a statistically insignificant downward trend in mean annual atmospheric pressure (0.2 hPa/10 years) from 1971 to 2010.